The influence mechanism of green advertising on consumers’ purchase intention for organic foods: the mediating roles of green perceived value and green trust - Li, Youyou; Shan, Baoshun (Frontiers in Sustainable Food Systems, 2025)
BackgroundIn the context of increasingly prominent global environmental issues, green consumption has gradually become an important component of sustainable development strategies. However, the mechanism through which green advertising, as a key medium for conveying environmental protection concepts, influences organic food purchase intention has not been systematically explored. This study focuses on how green advertising influences organic food purchase intention through the psychological and behavioral processes of consumers.MethodsBased on the Stimulus-Organism-Response (SOR) theory, this study constructs a relationship model between green advertising receptivity, green perceived value, green trust, and organic food purchase intention. Empirical data were collected through a questionnaire survey of Chinese consumers, and SPSS and AMOS software were used for data analysis to validate the applicability of the research model and test the hypotheses.ResultsA total of 447 valid samples were collected, and the measurement tools were found to be reliable and valid. The model fit indices indicated a good fit, adequately explaining the relationships between the variables. All research hypotheses received significant support, showing that green advertising receptivity has a significant direct effect on organic food purchase intention, as well as a significant indirect effect through green perceived value and green trust.ConclusionGreen advertising receptivity influences consumers’ purchase intention for organic food through the dual mediation mechanisms of green perceived value and green trust. This study provides theoretical support for the field of green advertising and consumer behavior and offers practical references for businesses to optimize green marketing strategies, enhance consumer trust, and foster value recognition.